The Future of the Music Business : How to Succeed with New Digital Technologies. - Gordon, Steve (MusicPro guides., 2015)
New technologies have revolutionized the music business. While these technologies have wreaked havoc on traditional business models, they've also provided new opportunities for music business entrepreneurs, as well as new challenges for musicians, recording artists, songwriters, record labels and music publishers. The Future of the Music Business provides a road map for success by explaining legal fundamentals including copyright law's application to the music business, basic forms of agreement such as recording, songwriting and management co ntracts, PLUS the rules pertaining to digital streaming, downloading and Internet radio. This book also shows exactly how much money is generated by each of these models, and details how the money flows to the principal stakeholders: artists, record labels, songwriters and music publishers.--Amazon.com.